HUBUNGAN PERSEPSI SISWA TERHADAP STRATEGI PEMBELAJARAN GURU DENGAN HASIL BELAJAR SENI RUPA DI SMP N 10 PADANG - Sri Wahyuni; Ernis Ernis (Serupa The Journal of Art Education, 2020)
This research goals to investigate the relationship between students' perceptions of teacher’s teach strategies and learning outcomes of Art and Culture subject matter Fine Arts, at SMP Negeri 10  Padang. The research is a correlational research with quantitative approach. This study used the product moment correlation analysis technique. The population was 800 students of SMP Negeri 10 Padang to determine the sample using the "Proportionate Stratified Random Sampling" techniqu . Hypothesis test results conducted on a sample of 260 students. Based on this results’s hypothesis is r count> r table (0.156> 0.113) there is a significant relationship, because sig is smaller than 0.05 obtained (0.012) means sig is accepted. Correlation test results have a positive and significant relationship on the Art and Culture subject matter Fine Arts of students of SMP Negeri 10 Padang.Kata Kuncii: Persepsi Siswa terhadap strategi pembelajaran guru, hasil belajar seni rupa.